2021
DOI: 10.1186/s13058-020-01384-6
|View full text |Cite
|
Sign up to set email alerts
|

Invasive lobular carcinoma of the breast: the increasing importance of this special subtype

Abstract: Invasive lobular carcinoma (ILC) is the most common of the breast cancer special types, accounting for up to 15% of all breast cancer cases. ILCs are noted for their lack of E-cadherin function, which underpins their characteristic discohesive growth pattern, with cells arranged in single file and dispersed throughout the stroma. Typically, tumours are luminal in molecular subtype, being oestrogen and progesterone receptor positive, and HER2 negative. Since last reviewing the lobular literature (McCart Reed et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
79
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(81 citation statements)
references
References 130 publications
1
79
0
1
Order By: Relevance
“…The Global Cancer Statistics reported that female breast cancer (BC) surpassed lung cancer as the most diagnosed cancer, with an estimated 2.3 million new cases (11.7%) (Sung et al, 2021). BC is generally regarded as a heterogeneous disease in terms of its molecular features, histological composition, and clinical characteristics (McCart Reed et al, 2021;Sadeghalvad et al, 2021). With the evolution of high-throughput technologies, we tend to subtype the disease into clinically relevant molecular subtypes, including normal-like, luminal A and B, HER2-enriched, and basallike or more intrinsic subtypes (Ochoa et al, 2020;Morgan et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The Global Cancer Statistics reported that female breast cancer (BC) surpassed lung cancer as the most diagnosed cancer, with an estimated 2.3 million new cases (11.7%) (Sung et al, 2021). BC is generally regarded as a heterogeneous disease in terms of its molecular features, histological composition, and clinical characteristics (McCart Reed et al, 2021;Sadeghalvad et al, 2021). With the evolution of high-throughput technologies, we tend to subtype the disease into clinically relevant molecular subtypes, including normal-like, luminal A and B, HER2-enriched, and basallike or more intrinsic subtypes (Ochoa et al, 2020;Morgan et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…As described by early cohort studies ( [12][13][14], reviewed in [8,15]), the most commonly altered driver mutations in ILC are in CDH1, TP53, PIK3CA, FOXA1, PTEN, TBX3, FGFR2, ERBB2, and ERBB3. AKT1 and CTNNA1 are increasingly important in ILC [16,17]; however, relatively low mutation frequencies were detected when profiled.…”
Section: Mutation Profiles Of Ilcmentioning
confidence: 99%
“…High resolution ILC genomic research has emerged over the last five years (reviewed in [8]), and the value of ILC sub-studies in clinical trials is undoubted. In order to facilitate detailed analysis of ILC, in the context of precision oncology, we present a meta-analysis of available ILC genomic datasets to develop a unified resource to inform further essential ILC research.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shed new light on ILC's different biology, clinical presentation, disease behavior, and metastasis [11,13,14]. Findings include differences in enriched molecular features in lobular tumors that could lead to future targeted therapies [15][16][17][18][19].…”
Section: Historic View Of Lobular Carcinoma Is Challenged By New Evidencementioning
confidence: 99%